The literature of connection - Trotter, David (Oxford University Press, 2020)
This text is about some of the ways in which the world got ready to be connected, long before the advent of electronic digital computing.
10.1093/oso/9780198850472.001.0001
Keywords: Literature; Motion pictures; Communication in literature; Communication in motion pictures